Representations of nurses regarding sexuality of women treated for breast cancer in Brazil - Elisabeth Meloni Vieira; Nicholas John Ford; Manoel Antonio dos Santos; Lílian Cláudia Ulian Junqueira; Alain Giami (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2013)
The development of new treatments has improved survival and quality of life among cancer patients. Nurses are expected to answer questions and to provide orientation regarding patients' sexuality since it is an important aspect of life. The main objective of this paper is to understand the representations of sexuality among nurses working with women who survive breast cancer after diagnosis and during treatment assuming that their representations may affect communication with the patient. This is a qualitative study using an in-depth guideline which involved interviews with 28 nurses living and working in the southeast of Brazil. The narratives were submitted to a content analysis and categories of representations were identified and are discussed here. Several representations of sexuality were found in the nurses' discourses. Some of the nurses' representations may be expected to hinder their ability to provide helpful orientation regarding the sexual lives of these patients.